A LOW TEMPERATURE SPECIFIC HEAT INVESTIGATION OF Cd Mn Se AND Cd Mn S (Journal of Sciences, Islamic Republic of Iran)
The specific heat of Cd Mn Se (x = 0.01) and Cd , Mn S (x = 0.026) in the temperature range of 0.3 - 40K was measured. The measurements were carried out in different applied magnetic fields (H = 0,10,20, 28KG). The results were analyzed with a model which includes long range interactions. Calculations based on on extended version of nearest neighbor pair approximation (including triplets) yielded a reasonable agreement with the experimental results. This approximation is seen to provide a good simultaneous description of the specific heat, susceptibility and magnetization results.